Developing a coupled turbine thrust methodology for floating tidal stream concepts: Verification under prescribed motion. (March 2020) - Brown, S.A.; Ransley, E.J.; Greaves, D.M.
Abstract: Floating systems offer an opportunity to expand tidal energy resource through an increase in viable sites and greater flow speeds near the free surface. However, the close proximity of the free surface provides uncertainty regarding power delivery and survivability due to the presence of waves, which could be addressed through a numerical model that is capable of considering all components of a floating tidal system simultaneously. This paper presents the first step in the development of such a tool: using the open-source CFD libraries of OpenFOAM as a basis, a computationally efficient HATT model has been developed for generalised incident flow conditions using actuator theory. A thorough evaluation of the model's sensitivity to key considerations in the simulation of entire floating tidal systems, such as flow speed and mesh alignment, showed that the model is robust, ensuring that it is suitable for future extension to wave-driven environments and integration into a framework for such systems. Highlights: A turbine model is developed for use in simulation of entire floating tidal systems. The model is integrated into the open source CFD software OpenFOAM. The model's accuracy is evaluated in steady flows and under arbitrary movement. The model is shown to be both accurate and insensitive to flow speed. The model is shown to be robust as it passes through the mesh.